Effects of berbamine on isolate myocardium in guinea pigs and humans - LI Ning-yuan; LI Wen-han; LI Yi-xiu (Acta Pharmacologica Sinica, 2016)
Berbamine depressed contractility and automaticity, prolonged the FRP without any influence on the excitability. Berbamine, like verapamil, did not antagonize competitively the positive inotropic actions of isoproterenol, histamine or CaCl2. The results suggest that berbamine is a calcium channel blocker from plant origin.